Impact of humic substances and nitrogen fertilising on the fruit quality and yield of custard apple - Cunha, Marcelo dos Santos; Cavalcante, Ítalo Herbert Lucena; Mancin, Adriana Cristina; Albano, Francisca Gislene; Marques, Adenaelson de Sousa (Acta Scientiarum. Agronomy, 2014)
The custard apple (Annona squamosa L.), also known as the sugar apple, is a fruit species native to Brazil that has been poorly studied, especially in relation to the effect of humic substances on its fruit quality and yield. An experiment was conducted from December 2010 to November 2011 to evaluate the fruit quality and yield of the custard apple as a function of nitrogen fertilising and the use of humic substances. The experimental design consisted of randomised blocks, with treatments distributed in a factorial arrangement (4 x 2), using four nitrogen doses (0, 100, 175 and 250 g of N plant-1) and two humic substance applications (with and without humic substances), with four replications. The fruit yield and fruit characteristics, such as fruit mass, titratable acidity (TA), soluble solids (SS), pulp pH and SS/TA ratio, were recorded. The humic substances and the nitrogen levels significantly affected the soluble solids, titratable acidity and SS/TA ratio, while the pH pulp was only influenced by the humic substances. The humic substances promoted a quantitative increase in the fruit yield of 0.63 ton ha-1. The fruit quality and yield of the custard apple depend on the nitrogen fertiliser and the interaction of the humic substances. Nitrogen fertilising of 100 g per plant, associated with humic substances, could be recommended for use in the production of custard apples.